2019
DOI: 10.1016/j.bpj.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ceramides and Lysophospholipids Cosegregate in Fluid Phosphatidylcholine Bilayers

Abstract: The mode of interactions between palmitoyl lysophosphatidylcholine (palmitoyl lyso-PC) or other lysophospholipids (lyso-PLs) and palmitoyl ceramide (PCer) or other ceramide analogs in dioleoylphosphatidylcholine (DOPC) bilayers has been examined. PCer is known to segregate laterally into a ceramide-rich phase at concentrations that depend on the nature of the ceramides and the co-phospholipids. In DOPC bilayers, PCer forms a ceramide-rich phase at concentrations above 10 mol%. In the presence of 20 mol% palmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…According to the manufacturer (Avanti Polar Lipids 57 ), this system is expected to yield samples with low polydispersity, if filters with pore size ≤ 200 nm are used. DLS measurements have confirmed this previously 58 and for the current samples (data not shown). Vesicle symmetry is expected to be maintained in the time between sample preparation and experiment.…”
Section: Methodssupporting
confidence: 90%
“…According to the manufacturer (Avanti Polar Lipids 57 ), this system is expected to yield samples with low polydispersity, if filters with pore size ≤ 200 nm are used. DLS measurements have confirmed this previously 58 and for the current samples (data not shown). Vesicle symmetry is expected to be maintained in the time between sample preparation and experiment.…”
Section: Methodssupporting
confidence: 90%
“…Recently, it has been shown that in the membrane environment ceramides co-segregate with lysophospholipids due to their large headgroup 79 . The interaction with large headgroup lipids not certified by peer review) is the author/funder.…”
Section: Long and Very Long Acyl Chain Ceramides Induce Cholesterol Independent Domain Formation In The Outer-leaflet Of Live Mammalian Cmentioning
confidence: 99%